The Effect of Differences of Opinion on Bank Interest, Education Level and Spiritual Intelligence on the Decision to Choose a Sharia Bank in Banyumas - Nurlaeli, Ida; Hasanudin, Hasanudin (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
This study aims to investigate whether the factors that influence people's decisions in choosing Islamic banks, especially bank interest views, level of education, perceptions of service, acceptance of promotions and spiritual intelligence, considering that Islamic banks have experienced development but seen from the market share are still small. This study uses a quantitative field approach, using a questionnaire distributed to 347 respondents who were selected in clusters around Purwokerto. The collected data were analyzed using logistic regression after first being tested with the overall model fit test and the coefficient of determination test. The results showed that the bank interest perspective, education level and spiritual intelligence had a significant effect, even though the bank interest perspective was negative. Islamic banks are advised to penetrate the market on consumers with a higher education background (S1) and consumers who have high spiritual intelligence. This study is the first study to use logistic regression on the Y variable.